2022
DOI: 10.3390/antiox11071387
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Lipid Dysregulation in Lipid Droplets: A Connection to Chronic Kidney Disease Revealed in Human Kidney Cells

Abstract: Chronic kidney disease (CKD), which is defined as a condition causing the gradual loss of kidney function, shows renal lipid droplet (LD) accumulation that is associated with oxidative damage. There is a possibility that an LD abnormality in quality plays a role in CKD development. This study aimed to explore the chemical composition of LDs that are induced in human kidney cells during exposure to free fatty acids as an LD source and oxidized lipoproteins as oxidative stress. The LDs were aspirated directly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…The role of oxidative stress is pivotal in the pathogenesis of renal disease. Chen et al (2022) reported multiple risk factors associated with the onset of kidney disease, which encompass oxidative stress, ectopic lipid accumulation, dyslipidemia, renal cell injury, and dysfunction. The development of different clinical disorders is believed to be influenced by lipid peroxidation that is triggered by free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The role of oxidative stress is pivotal in the pathogenesis of renal disease. Chen et al (2022) reported multiple risk factors associated with the onset of kidney disease, which encompass oxidative stress, ectopic lipid accumulation, dyslipidemia, renal cell injury, and dysfunction. The development of different clinical disorders is believed to be influenced by lipid peroxidation that is triggered by free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid droplet deposition leads to renal cell energy depletion and ultimately endogenous renal cell apoptosis, leading to CKD. 34 This may explain the significant association between LE8 and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…A declining trend in the PC/TG ratio, a sign of LD abnormalities, was seen. It's crucial to mention that PE did not exhibit the trend of depletion, only PC did (Chen et al, 2022). In an experiment to better understand the role of lipids in different metabolic functions during kidney aging, phosphatidylcholine (PC) levels were shown to be declining in the kidneys of elderly mice, according to the results of the investigation (Noh et al, 2019).…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%